Causal Relation of Psychical Stress to Acute Back Pain - Hajnovic, L; Knöller, S; Schütz, L (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2018)
PURPOSE OF THE STUDY There s a known relation between the chronical back-pain-syndrome and psychical problems. We suppose a direct causality between acute stress and onset of the backpain syndrome. MATERIAL AND METHODS A prospective cohort-study (IV/2014 - VIII/2014) of patients who came to our emergency department with acute backpain-syndrome, with no relevant previous history - such as operations or chronic pain. We questioned together 39 patients (19 female and 20 male). The patients filled in two charts: FW7, and also a modified HADS-D. In the later one the patients were questioned in two extra points regarding contingent excessive emotional or existential problems in their brief history. The Pain-Severity-Score was assessed as well. RESULTS Combined together, relevant score-results and / or anamnesis of excessive emotional or existential problem was found in 79.5% (SD 0.4%) of the whole cohort. CONCLUSIONS This could have implications for guidelines, introducing the psychotherapy-first into the concepts. Key words:stress; well-being; depression; back-pain-syndrome.
Keywords: akutní bolest; Surveys and Questionnaires; Pain Measurement; urgentní služby nemocnice; Humans; lidé středního věku; Acute Pain; Female; dospělí; lidé; průzkumy a dotazníky; Medical History Taking; Stress, Psychological; Adult; Back Pain; ženské pohlaví; Male; Middle Aged; anamnéza; psychický stres; bolesti zad; mužské pohlaví; Emergency Service, Hospital; měření bolesti